Clasificador basado en Máquina de Vectores de Soporte Ajustada para Reconocimiento de Peatones en Tráfico Urbano - Roncancio, Henry A; Carmona Hernandes, André; Archila, John Faber; Becker, Marcelo (Ingeniería, 2012)
The need for autonomy and intelligent decision-making in automobile flow is booming. For this purpose there are a number of interesting problems related to recognition of features in urban environments. One of the main relevant aspects in this subject is the recognition of pedestrians, a technology that is expected to save millions of lives avoiding or decreasing the rates of pedestrian run away. In this paper we propose the recognition of pedestrians in urban environments using a classifier based on a Support Vector Machine. We used up to 5000 images from the INRIA database to train the classifier and validate its accuracy through the cross-validation method.